Robot Racking : A Racking Solution for Autonomous Production - Envall, Zakarias (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
As an engineering student, the most natural way of summarizing this thesis project is by relating it to a mathematical equation. The solution to this equation is given, and it is in the form of a racking concept that enables the use of robots. The other side of the equation is however a bit more complex. This side contains several undefined variables, which can only be solved by delving into various theoretical fields and exploring unchartered depths of the creative space.The project’s main objective is to design a concept rack for Gestamp HardTech in Luleå, Sweden, for storage and in-house transport of the beams which are produced at the HardTech facility. The rack is meant to be loaded both into and out of by robots and should suit an as wide array of beams as possible. To determine the possibilities and limitations of the rack’s robot-user, several automation aspects are researched, centered on industrial robots and machine vision. The beams which are produced at the Gestamp HardTech Luleå production plant today are analyzed, whereby twelve of them are ultimately chosen for the rack’s design to be focused on. What follows this is a creative process consisting of a creative idea-generating phase, an evaluative phase focused on implementation of the ideas, and a refinement phase where the rack concept is finalized. The process includes various methods of idea generating, a great deal of sketching, physical testing of the concepts, and finally CAD-modeling. The result, named 4.0-Rack, is in the form of a modular rack-concept which balances the aspects of flexibility, by suiting ten of the reviewed beams, with a high packing-grade, providing a mean packing-grade of 83% in relation to the way the beams are currently packed.